2016
DOI: 10.1016/j.compositesa.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the changes in bending stiffness of a textile reinforced composite due to in-plane fabric shear: Part 1 – Experiment

Abstract: A study to investigate the factors that contribute to the variation among the stiffnesses of consolidated composite plates reinforced by plain-weave fabrics with various degrees of in-plane shear is presented. The first part of the two-part study focuses on the experiments performed. Threepoint bend tests were used to measure the effective stiffness of the composite plates along the global X and Y axes, which were aligned with the weft and warp orientations, respectively, in the undeformed configuration at 0° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…All of the plates in the current study were reinforced by a single-ply of a plain-weave fabric [38]. Three-point-bend tests performed on the plates resulted in similar curvatures for equivalent positive and negative moments, confirming symmetry of the specimens about the neutral surface.…”
Section: Application Of Classical Laminate Theorysupporting
confidence: 54%
See 3 more Smart Citations
“…All of the plates in the current study were reinforced by a single-ply of a plain-weave fabric [38]. Three-point-bend tests performed on the plates resulted in similar curvatures for equivalent positive and negative moments, confirming symmetry of the specimens about the neutral surface.…”
Section: Application Of Classical Laminate Theorysupporting
confidence: 54%
“…Part 1 of this investigation [38] described the manufacture of composite plates reinforced by textiles with various degrees of in-plane shear. The current work will refer to two coordinate systems defined by the plates' geometries, as depicted in Fig.…”
Section: Critical Investigation Of the Factors Influencing Flexural Smentioning
confidence: 99%
See 2 more Smart Citations
“…Kim, D. H., Kim, H. G. and Kim, H. S [27] designed and manufactured hybrid glass/carbon composite bumper beam was via the design optimization process combined with the impact analysis. In the study of Cynthia Mitchell, Lisa Dangora, Christie Bielmeier and James Sherwood [28], investigations were pursued in an effort to understand the relationship between changes in the stiffness of plain-weave fabric-reinforced plates and the degree of in-plane shear within the fabric reinforcement. They identified that fabric shearing will result in several major changes within the reinforcement geometry that the reorientation of the fibers within the plane of the plate, the increase in plate thickness with increasing shear angle, and the change in the tow cross-sectional shape and orientation.…”
Section: Developed a Finite Open Journal Of Composite Materialsmentioning
confidence: 99%